1990
DOI: 10.1007/bf01612994
|View full text |Cite
|
Sign up to set email alerts
|

Effects of antineoplastic phospholipids on parameters of cell differentiation in U937 cells

Abstract: The proliferation of the human promonocytic leukemia cell line U937 is inhibited by several ether lipids, ether lipid analogues and by phorbol esters. An early effect of this retardation of cell growth is the induction of a basic chromosomal protein, histone H1(0). Northern blot analysis of H1(0) mRNA levels reveals an increase of the mRNA concentration within a few hours after addition of hexadecylphosphocholine and 1-O-octadecyl-2-O-methyl-rac-glycero-3-phosphocholine. This early effect on the synthesis of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1

Year Published

1992
1992
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 48 publications
1
11
1
Order By: Relevance
“…These results theoretically confirm evidence that phospholipids have anticarcinogenic activities (Koufaki et al, 1996;Hochhuth et al, 1990). Finally, the study by Ferreira and colleagues (2013c) of the antileukemic properties of PHOS-S also corroborates findings by Dhakshinamoorthy et al (2015) of a possible role of PHOS-S in the inhibition of leukemic cells.…”
Section: Discussionsupporting
confidence: 82%
“…These results theoretically confirm evidence that phospholipids have anticarcinogenic activities (Koufaki et al, 1996;Hochhuth et al, 1990). Finally, the study by Ferreira and colleagues (2013c) of the antileukemic properties of PHOS-S also corroborates findings by Dhakshinamoorthy et al (2015) of a possible role of PHOS-S in the inhibition of leukemic cells.…”
Section: Discussionsupporting
confidence: 82%
“…Besides its pronounced antiproliferative activity in vitro and in vivo (10,29), the compound induces differentiation of leukemic cell lines into mature myeloid cells (15), and some data suggest that induction of differentiation may contribute to the in vivo antitumor activity of He-PC (13). From experiments on normal peripheral mononuclear cells, it was concluded that He-PC may possess immunomodulatory activity, acting as a costimulator for the interleukin-2-mediated T-cell activation process (32).…”
Section: * Corresponding Authormentioning
confidence: 99%
“…By direct action, these compounds were shown to influence membrane fluidity, 27 inhibit protein kinase C, 28 modulate phosphatidylcholine biosythesis, 29 inhibit phospholipase, 30 elevate intracellular calcium concentration, 31 regulate signal transduction 32 and inhibit tumor cell growth either in vitro or in vivo. 1,21,[33][34][35][36] As for the indirect effects, these substances have been reported to induce tumor cell differentiation and differentiation of myelomonocytic cells [13][14][15] and to activate macrophages. 10,16,17,[37][38][39] Since most of the studies dealing with HPC-mediated macrophage activation were performed in vitro, it was unclear until now in how far this mechanism substantially contributes to the antitumor effect that has been observed in several human tumor models.…”
Section: Discussionmentioning
confidence: 99%
“…HPC was described to influence tumor and monocyte differentiation as well as induction of cytokines and macrophage/Kupffer cell activation in vitro. 10,[12][13][14][15][16][17][18]40 Although a number of studies report the activation of macrophages by L-HPC in vitro, there has been no direct proof for the active participation of the activated cells in the antitumor mechanism in vivo. The interest of this study, therefore, was focused on whether macrophages actively infiltrate tumors under an HPC therapy and which mechanisms they utilize to possibly inhibit tumor growth.…”
mentioning
confidence: 99%